1989
DOI: 10.2307/1938094
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Development and Leaf Nitrogen Distribution in a Stand of Carex Acutiformis

Abstract: Seasonal changes in leaf nitrogen distribution were examined in the canopy of a Carex acutiformis stand in a wet meadow area. Although there was a tendency for leaf nitrogen concentration to decrease with increasing leafage in any one layer of the canopy, nitrogen concentration increased significantly with plant height despite increasing age of leaf portions higher in the canopy. This suggests a predominant effect of the light climate on the nitrogen distribution within the canopy. During the growing period, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(46 citation statements)
references
References 11 publications
2
43
0
1
Order By: Relevance
“…Later in the rainy season ring growth is much less (Worbes 1999). This may be due to decreasing photosynthetic capacities of older leaves (Mooney et al 1981;Hirose et al 1989;Ackerly and Bazzaz 1995;Miyaji et al 1997) or to a shift from growth to storage (Iwasa and Cohen 1989). These factors, or a combination of these factors, most probably explain why early rainfall is so important for tree growth that year.…”
Section: Relationship Between Tree Growth and Rainfallmentioning
confidence: 99%
“…Later in the rainy season ring growth is much less (Worbes 1999). This may be due to decreasing photosynthetic capacities of older leaves (Mooney et al 1981;Hirose et al 1989;Ackerly and Bazzaz 1995;Miyaji et al 1997) or to a shift from growth to storage (Iwasa and Cohen 1989). These factors, or a combination of these factors, most probably explain why early rainfall is so important for tree growth that year.…”
Section: Relationship Between Tree Growth and Rainfallmentioning
confidence: 99%
“…As new leaves are produced at top of the plant, which is exposed to full irradiance, and as young leaves are usually high in protein content, leaf age was suggested to control the allocation program (Field, 1983;Field and Mooney, 1983), although the effect of ageing was different in extent between species native to closed habitats and those native to open canopy habitats (Mooney et al, 1981). Hirose et al (1989) studied nitrogen distribution in a stand of a monocotyledonous species, Carex acutiformis. As this species is a rosette plant having a meristem at the base of the plant, the youngest portion of a leaf blade is always subject to the lowest irradiance within the canopy.…”
Section: E a F N I T R Og E N D I S T R I B U T I O N A Nd C A No Pmentioning
confidence: 99%
“…Given this, it can be shown that resource use is optimized when the distribution of nitrogen within the canopy is directly proportional to the distribution of intercepted PAR, when both are expressed on an area basis (e.g., Farquhar 1989). Many plant canopies have now been studied from this perspective (Field 1983, Hirose et al 1989, Hollinger 1989, Ellsworth and Reich 1993, Evans 1993, Kull and Niinemets 1993, and in nearly all cases, it has been found that nitrogen per unit leaf area varies in parallel with light availability, although it rarely decreases sharply enough to remain proportional to light at lower levels of the canopy. However, these theories do not specify the physiological or morphological mechanism by which an optimal distribution is obtained, and structural variations above the level of the leaf have rarely been considered.…”
Section: Introductionmentioning
confidence: 99%